Ticari Bankalarda maliyet etkinliği, teknolojik ilerlemeler, ölçek ve alan ekonomileri: Türk Ticari Bankacılık Sektörünün analizi - (:unkn) unknown (My University, 2011)
Bu çalışma, Türk Bankacılık Sektöründe 1997-2010 döneminde maliyet etkinliği, teknolojik ilerleme, ölçek ve alan ekonomilerini analiz etmeyi amaçlamıştır. Çalışmada ekonometrik analiz yöntemleri olarak ölçekleri belirlemek için k-ortalama tekniği ve katsayı tahminleri için de tesadüfî sınır modelleri kullanılmıştır. Elde edilen bulgulara göre; ele alınan dönemde bankaların genel maliyet etkinliklerinin yüksek olduğu belirlenmiştir. Dahası elde edilen sonuçlar, sektörde çok güçlü ölçek ekonomilerinin varlığına işaret etmektedir. Bulgular, ayrıca teknolojik ilerlemelerin incelenen dönemde arttığını ve sektörde alan ekonomilerinin güçlü etkileri olduğunu göstermektedir.

This study aims to analyse cost efficiency, technological progress, economies of scale and economies of scope for Turkish Banking Sector over the 1997-2010 period. In the study be used as econometrical analysis technics both k-mean cluster to appear the scales and stochastic frontier models to estimate the parameters. According to our empirical findings, overall the cost efficieny of all banks during this period was high. Moreover results indicate to exist most powerful economies of scale in sector. Results also indicate that technological progress has not increased during the research period and even there had powerful effects of scope economies in the sector, but these effects were not be dominant.
Cost efficiency, technological progresses, economies of scale and scope in commercial Banks: analysis of Turkish Commercial Banking Sector
Keywords: İşletme